2004
DOI: 10.1097/01.ten.0000123564.40707.84
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Screening and Treatment of Osteoporosis

Abstract: Evidence exists that many at-risk patients are not screened or receive appropriate therapy for osteoporosis. We reviewed studies of bone mineral density (BMD) testing and osteoporosis therapy to describe predictors associated with screening and treatment of osteoporosis. We performed a structured review, searching MEDLINE and HEALTHStar from 1992 through 2002 using appropriate terms. Two authors examined all retrieved articles, and relevant studies were reviewed with a structured data abstraction form. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
0
5
1
Order By: Relevance
“… 19 , 20 Our observation that osteoporosis screening was more likely in women than men is also consistent with earlier studies. 18 , 21 Our finding that osteoporosis screening was no more likely in white adults than black adults, when adjusting for other osteoporosis risk factors, is different from findings of several previous studies and warrants further study. 18 , 22 …”
Section: Discussioncontrasting
confidence: 84%
“… 19 , 20 Our observation that osteoporosis screening was more likely in women than men is also consistent with earlier studies. 18 , 21 Our finding that osteoporosis screening was no more likely in white adults than black adults, when adjusting for other osteoporosis risk factors, is different from findings of several previous studies and warrants further study. 18 , 22 …”
Section: Discussioncontrasting
confidence: 84%
“…Multiple previous studies suggest that older individuals are either less likely or no more likely than younger individuals to be treated for osteoporosis [ 18 – 21 ]. A few studies have found that younger patients are less likely to receive pharmacologic treatment for osteoporosis than older patients, but this discrepancy may be secondary to the use of younger age cutoffs to distinguish older from younger patients in these particular studies (e.g., postmenopausal vs premenopausal) [ 22 24 ]; our study focused on an older population of individuals, those age 60 and older. Our finding that individuals with prolonged oral steroid use may not be receiving sufficient osteoporosis treatment concurs with that of other studies [ 22 , 25 , 26 ], as does our finding that osteoporosis treatment was more likely in women than men [ 18 , 21 – 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Only 23% of women 55 years or older received pharmacological treatment following a fracture, 5 and nearly half of the women 45 years or older did not initiate pharmacological treatment within 6 months after a bone mineral density (BMD) test confirming osteoporosis or osteopenia. 6 Previous studies have evaluated the patterns of osteoporosis treatment among patients diagnosed with osteoporosis 3,4,[7][8][9][10][11] and estimated the number of individuals who should be considered for osteoporosis treatment. 2,[12][13][14] However, to our knowledge, no studies have assessed the pattern of osteoporosis treatment among those who meet the NOF criteria for pharmacotherapy but may not have been previously diagnosed or aware of their BMD measurement and osteoporosis risk.…”
Section: Introductionmentioning
confidence: 99%